Influence of Oxidative Stress Erythrocyte State at Hypothermic Storage - Holovina, Kseniia M.; Kovalenko, Igor F.; Bobrova, Olena M. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 180.